Searching for music: understanding the discovery, acquisition, processing and organization of music in a domestic setting for design. Issue 4 (August 2016) - Chamberlain, Alan; Crabtree, Andy
Abstract This series of studies make it clear that a wide range of both physical and digital resources are involved in domestic music consumption. The selection of digital resources is particularly evident, and it can be observed that domestic music consumption is afragmented business, taking advantage of many different "channels" for getting, using and preparing music. While there are not a series of common channels, each home displayed a variety of methods in respect to using metadata in multiple different modalities: regardless, the activities involved in getting, using and preparing musiccohere through a noticeable, emergent set ofworkflows . We find that not only does metadata support searching, as one might expect, but also it pervades all parts of the workflow and is used in real-time as a reflexive artifact and in terms of its future perceived/prescribed use. The findings of the research raise a series of possibilities and issues that form the basis for understanding and designing for metadata use.